Assessing the Child–Parent Relationship Between Working and Non-working Mothers in a Selected Community of Bhubaneswar - Kshirabdhi Tanaya; Sakuntala Giri; Meghna Mishra; Subhashree Moharana (International Journal of Evidence Based Nursing And Practices, 2023)
Introduction: Two categories of mothers exist: those who work outside the home, referred to as working mothers, and those who stay at home, often described as housewives. Working mothers may allocate quality time to their children, even if the amount of time is not necessarily large. On the other hand, non-working mothers not only manage household responsibilities but also provide care for their children and the entire family. Methods: A non-experimental comparative research was carried out in the Baramunda urban community, aiming to achieve the following objectives: 1. Assess child–parent relationships in both working and non-working mothers. 2. Compare child–parent relationships between working and non-working mothers. 3. Investigate potential associations between child–parent relationships in working and non-working mothers and various demographic variables. The study involved a total of 100 participants who were selected using a non-probability purposive sampling method. Results: In analysis, study result revealed that the majority (82%) of working mothers were having average level of child parent relationship and 76% of non-working mothers were having average level of child parent relationship. Result also evaluated that there was significant association between level of child–parent relationship in working mothers with type of job (χ2=7.027, p=0.008), type of family (χ2=5.767, p=0.016) and the significant association found between level of child–parent relationship in non-working mothers with type of family (χ2=4.778, p=0.043). Discussion: In 2017, the researcher concluded that children with non-working mothers exhibit superior social, emotional, and domestic adjustment compared to children with working mothers. Conclusion: Study concluded that there is average level of child parent relationship among both working and non-working mothers.
Keywords: Working mother; child–parent relationship; non-working mother; quantitative